Actual Problems of the International Forensic Cooperation - Sh. N. Khaziev (Теория и практика судебной экспертизы)
The article deals with the historical stages of development of international cooperation in the field of forensic activities, questions of its legal regulation in the Russian Federation at the present stage, as well as a strategy for further development of this cooperation. Identified five major historical stages in the development of international cooperation in the field of forensics. In order to create the legal basis of international forensic cooperation invited to complete a draft federal Law «On forensic activities in the Russian Federation» the rules on carrying out forensic examinations of Russian experts for international justice institutions, the forensics examinations with the involvement of forensic experts of a foreign State, on the participation of Russian forensic experts in foreign and international non-governmental scientific and professional organizations of forensic experts. Proposed strategy for the development of international cooperation in the field of forensic activities.